Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/cdq.12089
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Negative Career Thoughts to Depression and Hopelessness

Abstract: Although some research literature focuses on the integration of mental health and career counseling, there has been little that examines both areas in relation to depression and hopelessness. This study investigated the relationship among dysfunctional career thinking, depression, and hopelessness in a sample of 139 undergraduate and graduate students seeking drop‐in or individual career counseling services at a university career center. The authors found that two aspects of dysfunctional career thinking, deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…CIP theory has been used in over 180 empirical studies (Sampson, Reardon, Peterson, & Lenz, 2019) and has been credited as the theory with “probably the most widely studied career interventions” (Brown, 2015, p. 62). Much research has focused on dysfunctional career thinking (e.g., Bullock‐Yowell, Peterson, Reardon, Leierer, & Reed, 2011; Leierer, Wilde, Peterson, & Reardon, 2016), consistently showing negative effects on variables such as career decidedness and life stress (Bullock‐Yowell et al, 2011), career decision state (Leierer et al, 2016), depression (Dieringer, Lenz, Hayden, & Peterson, 2017), and neuroticism (Kelly & Shin, 2009). Still, validation of the relationships among these four components and their impact on an individual's career decision‐making abilities is needed.…”
Section: A Cognitive Information Processing Theory–based Coursementioning
confidence: 99%
“…CIP theory has been used in over 180 empirical studies (Sampson, Reardon, Peterson, & Lenz, 2019) and has been credited as the theory with “probably the most widely studied career interventions” (Brown, 2015, p. 62). Much research has focused on dysfunctional career thinking (e.g., Bullock‐Yowell, Peterson, Reardon, Leierer, & Reed, 2011; Leierer, Wilde, Peterson, & Reardon, 2016), consistently showing negative effects on variables such as career decidedness and life stress (Bullock‐Yowell et al, 2011), career decision state (Leierer et al, 2016), depression (Dieringer, Lenz, Hayden, & Peterson, 2017), and neuroticism (Kelly & Shin, 2009). Still, validation of the relationships among these four components and their impact on an individual's career decision‐making abilities is needed.…”
Section: A Cognitive Information Processing Theory–based Coursementioning
confidence: 99%
“…Based on CIP theory (Sampson et al, 2004) and Beck's (1976) cognitive therapy approach, the Career Thoughts Inventory (CTI; Sampson et al, 1996b;Sargent & Lenz, 2017-2018 was developed to measure negative career thinking in career problem-solving and decision-making. Research on negative career thoughts has found significant relationships with decision-making style and cognitive thought patterns (Paivandy, Bullock, Reardon, & Kelly, 2008), depression (Saunders, Peterson, Sampson, & Reardon, 2000), hopelessness (Dieringer, Lenz, Hayden, & Peterson, 2017), and vocational identity (Strohm, 2008;Yanchak, Lease, & Strauser, 2005).…”
Section: March 2019 • Volume 67mentioning
confidence: 99%
“…Harris and Rottinghaus (2017) found that the General Occupational Themes and Personal Style Scales of the Strong Interest Inventory (Donnay, Morris, Schaubhut, & Thompson, 2004) accounted for significant variance in respondents’ subjective well‐being. Dieringer, Lenz, Hayden, and Peterson (2017) found that subscale scores of Decision‐Making Confusion, Commitment Anxiety, and External Conflict on the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996) all had significant positive correlations with the total scores on the Beck Depression Inventory–II (Beck, Steer, & Brown, 1996) and the Beck Hopelessness Scale (Beck, 1993).…”
Section: Complexity Of Career Development Concernsmentioning
confidence: 99%